Peluang dan Ancaman Otonomi Desa Pasca Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Muhadam Labolo (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2017)
The changes about Village policy provide both opportunities and threats to the development of village autonomy. Opportunities for the development of village autonomy are at least normatively gaining a foothold from two important principles of recognition and subsidiarity. The first principle as a form of recognition of village existence in various forms has actually been introduced through Law Number 22 Year 1999 and 32 Year 2004 which corrects efforts to uniform the lowest government entity of the village under another name. The second principle is the juridical consequence of the 1945 Constitution article 18B paragraph (2) where the state not only recognizes, also respects special and special units as long as it is still there and well maintained. This principle allows the state to allocate resources to the village even though the village is no longer subordinate to the state (mini bureaucracy) as the practice of Law 5/1979 through local state government paradigm. With the resources referred to the village at least have the opportunity to develop the original autonomy (self governing community) and not solely under the control of local governance system (local self-government). The allocation of resources from the government, provincial and district / city and the opening of access in the effort of developing village autonomy is not impossible to increase the tension in the village through abuse of authority and the potential of horizontal conflict. Village autonomy can ultimately contain threats if a number of important requirements can not be fulfilled given the culture, structure and environment that affect the village is much more dominant than the supradesa itself is quite distant with the community.Keywords: village autonomy, opportunities, threats